The Implementation of the Green Building Concept in the Design of the Politeknik Pelayaran Bangka Belitung. - Tiara Millenia Loziska; Zuber Angkasa; Sabrina Alifia Zahra (Talenta Publisher, 2024)
The province of Bangka Belitung Islands requires a high-quality human resource pool in the field of shipping and nautical studies. To support the education and competency development of human resources in the maritime sector, the construction of the Politeknik Pelayaran Bangka Belitung (POLTEKPEL BABEL) is deemed necessary. POLTEKPEL BABEL is envisioned to be a sustainable school building, characterised by its lower consumption of energy, water, and resources, as well as reduced waste generation compared to conventional buildings. This research focuses on the implementation of the green building concept in the design of POLTEKPEL BABEL. The study employs a quantitative descriptive method and a design method that integrates systems with existing ecological processes on-site, including orientation, wall-to-window ratio (WWR), the cumulative value of Roof Thermal Transfer Value (RTTV) and Overall Thermal Transfer Value (OTTV), as well as technical planning assessments for green buildings. Both primary and secondary data are utilised in this research. The findings indicate that the design of POLTEKPEL BABEL incorporates the principles of green building by considering various indicators outlined in the technical guidelines for green building assessment. These indicators encompass site management, energy usage efficiency, indoor air quality, the use of environmentally friendly materials, and waste management. Consequently, the implementation of these principles in the design of POLTEKPEL BABEL is expected to support sustainable development encompassing environmental, energy, and occupant well-being aspects.